Analysis of the role of General Practice in preventing Avoidable Hospitalisation through a multilevel approach - Aldo Rosano; Walter Ricciardi; Jouke van der Zee (Epidemiology, Biostatistics and Public Health)
Objective. To examine the relationship between Avoidable Hospitalisation (AH) and the activities of General Practitioners (GPs). The study was carried out in the Lazio Region (Italy) within different organizational models of primary care (PC) delivery.